Pengaruh Kemampuan Numerasi Terhadap Hasil Belajar Matematika Siswa UPTD SMPN 22 Barru - Heriyanti Heriyanti; Sriyanti Mustafa; Vernita Sari (Prodi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Muhammadiyah Parepare, 2023)
This type of research is a mixed method research. Aims to determine the effect of numeracy skills on the mathematics learning outcomes of class VIII UPTD SMPN 22 Barru. The population of this study were students of class VIII consisting of 5 classes. The sample in this study was class VIII.1, totaling 25 people, using cluster random sampling. This research data was obtained using research instruments in the form of test sheets and interviews. Data collection techniques used are test techniques and interview techniques. The results of the statistical descriptive analysis showed that the numeracy skills of class VIII UPTD SMPN 22 Barru based on indicators of numeracy ability were in the good category with a percentage of 70.2% with the first indicator, namely using various numbers or symbols related to basic mathematics in the good category with a percentage of 72 % as many as 18 students. The second indicator, namely analyzing information presented in various forms (tables, diagrams, etc.) is in the sufficient category with a percentage of 60% for 15 students. The third indicator, namely interpreting the results of the analysis to predict and make decisions, is in the good category with a percentage of 78.6% for 20 students. The results of inferential statistical analysis using the one sample t-test obtained a significant value of p = 0.000 < α = 0.05, this means that H0 is rejected and H1 is accepted. So, it can be concluded that numeracy skills have a positive effect on the mathematics learning outcomes of class VIII UPTD SMPN 22 Barru.